2020
DOI: 10.1016/j.transci.2019.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for stem cell mobilization failure in multiple myeloma patients: A single center experience

Abstract: Background and aim: High-dose chemotherapy followed by autologous stem cell transplantation (ASCT) has been considered the standard of treatment care for patients with multiple myeloma (MM). Insufficient mobilization and harvest of peripheral stem cells can be a major obstacle for performing ASCT. This is resulting in a lacking opportunity of cure in patients with MM. The aim of this study was to evaluate the factors which influence mobilization failure in patients with MM. Materials and methods: This study ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In the present study, this collection goal was unmet in only 4 of 790 patients (0.5%). As demonstrated in most previous analyses, age does not seem to be associated with mobilization failure (<2 × 10 6 CD34 + cells/kg) [37, 43, 45]. However, some studies indicate an adverse effect [41, 44].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the present study, this collection goal was unmet in only 4 of 790 patients (0.5%). As demonstrated in most previous analyses, age does not seem to be associated with mobilization failure (<2 × 10 6 CD34 + cells/kg) [37, 43, 45]. However, some studies indicate an adverse effect [41, 44].…”
Section: Discussionmentioning
confidence: 79%
“…The present study indicates that age >60 years is disadvantageous with higher collection goals (4 or 6 × 10 6 CD34 + cells/kg). We identified two other previous studies that considered the ISS stage; however, it was not associated with mobilization failure [43, 46] . In the present study, ISS stage III was associated with a lower probability of reaching the collection goal of ≥6 but not ≥4 × 10 6 CD34 + cells/kg.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our results found that gender, disease subtype, ISS stage, treatment regimen, disease status, number of sessions, and presence of diabetes did not significantly affect CD34 + cell harvest yield, success rate, or quality, which aligns with the findings of some previous reports. 16 , 17 In contrast, when patients were ≤55 years old, the number of CD34 + cells collected, and the collection success rate were better than for those aged >55 years old. This demonstrated that younger patients might have a better reserve capacity for HSCs, so more HSCs could be released when mobilized for collection.…”
Section: Discussionmentioning
confidence: 95%
“…Sensitivity analysis was performed using different definitions of mobilization failure to identify risk factors of CD34 + cell count yield <2 × 10 6 cells/kg [ 29 , 30 , 31 ], as well as CD34 + cell count collected being less than 5 × 10 6 cells/kg [ 32 , 33 , 34 ]. All data management and statistical analysis were performed using SAS 9.4 software (SAS Institute Inc., Cary, NC, USA) and STATA statistical software, version 15.1 (StataCorp, College Station, TX, USA).…”
Section: Methodsmentioning
confidence: 99%